ANALYSIS OF CAUSES AND EFFECTS OF ROAD TRANSPORT ACCIDENTS ALONG ZARIA-SOBA ROAD KADUNA STATE, NIGERIA - Moses Adedokun, Olutoyin; Olufunmilayo Bello, Aduke; Dyaji, Rifkatu; Uwanuakwa, Angela; Aliyu, Abdulhadi (African Journal of Social and Behavioural Sciences, 2024)
This work examines the locations, causes and effects of road traffic accidents along the Zaria- Soba highway in Kaduna State, Nigeria. The data used for the study were obtained from people along the route. Using simple random sampling, questionnaires were administered to the respondents. A total of 150 questionnaires were administered in ten selected villages along the route. Descriptive statistics, especially percentages and tables, were used to analyse the data. The results of the study showed that the major causal factor of accidents along the route is bad road, 58.7%, 22.7% was as a result of careless driving, 6.5% was due to overspeeding, drunkenness accounts for 3.3%, lack of regard for road signs due to illiteracy account for 2.0%. It was also discovered that 35% of the accidents occurred between 1.00 pm and 4.00 pm, 26.5% occurred mostly at night (5-10 pm), and 13.5% occurred in the morning. It is, therefore, suggested that the government reconstruct the route or, in the short run, refill the potholes, especially in areas with high cases of accidents. Public awareness and traffic education, such as the use of seat belts, interpretation of road signs, regular vehicle checks, etc., should be carried out by the FRSC. Road infrastructure, such as road signs and pedestrian bridges that need to be improved along the study route, should be provided, with a view to making the Zaria- Soba route accident-free.